Effect of Wing Locations to the Aerodynamic of UiTM’s Blended Wing Body-Unmanned Aerial Vehicle (BWB-UAV) Prototype - Diyana Nasri Huang, Farah; Wisnoe, Wirachman; Effendy Mohd. Nasir, Rizal; Sabah Shukri Askari, Ehan (International Journal of Engineering and Technology, 2018)
This paper focuses on the effect of wing placement on UiTM’s BWB Prototype to the aerodynamic performance of the aircraft. Lift coefficient (CL), drag coefficient (CD) and pitching moment coefficient (CM) are analyzed at 20 m/s air velocity, using NUMECA Computational Fluid Dynamics (CFD) software. Three wing locations are selected, i.e.: initial location (in reference to the BWB Prototype), front location (30% from leading edge), and middle location (in between of the first two cases). The canard and wing tips from the BWB Prototype are removed for this study. Grid independence study is completed to observe the effect of number of cells on the computation results. Comparison between the CFD and wind tunnel results on the initial BWB Prototype is performed for validation purpose. The variation of CL, CD and CM are presented in curves of lift coefficient, drag coefficient and pitching moment coefficient against angles of attack (α). The lift coefficient curves give similar trends for the three wing locations and the initial configuration except between 20° – 35° angles of attack where different fluctuation behavior occurs on the curves. The maximum lift coefficient obtained is around 0.86 – 1.05 at α = 26° – 30°. Drag coefficient curves also show similar trend for the three wing locations, but lower than the initial configuration due to removal of the canard and wing tips. The pitching moment curves show significant difference in slope among the three placements of the wing for α above 10°. The pitching moment coefficient curves indicates negative slopes up to of α = 18° (initial and middle case) and α = 22° (front case) which indicates static stability for all cases. Curves show that the middle wing configuration continues to give static stability up to higher angles of attack whereas the front case provides the best static stability up to α = 22°. Overall the absence of canard and wing tips removes the sudden change of slope of pitching moment around α = 12° which initially occurs on the BWB-UAV Prototype.